Proteomics Analysis of Five Potential Plasma-derived Exosomal Biomarkers for Acute Myocardial Infarction - Xu, Shasha; Zhai, Yi; Wang, Chen; Zhang, Yang; Liu, Xiaowei; Jiang, Jianjun; Mi, Yafei (Current Medicinal Chemistry, 2025)
AimsThis study was to explore the relationship between plasma exosomes and Acute myocardial infarction (AMI).BackgroundAcute myocardial infarction (AMI) is one of the most common cardiovascular complications. Recent studies have shown that exosomes play a crucial role in the development and progression of cardiovascular diseases. However, there is a lack of relevant research on the relationship between plasma exosomes and AMI.ObjectiveThis study was designed to explore the relationship between plasma exosomes and AMI.MethodsThis retrospective study collected the basic clinical data of patients with AMI (n = 10), stable angina pectoris (SAP, n = 10), and noncoronary heart disease (CON, n = 10) at the Department of Cardiovascular Medicine at Taizhou Hospital (Zhejiang, China, 2021.01 to 2021.12). Proteomics was used to systematically screen the differential proteins of plasma exosomes in patients with clinical AMI, SAP, and CON. Then, the results were further verified using parallel reaction monitoring (PRM).ResultsFive of all the differentially expressed proteins (DEPs) were quantified by PRM. Compared with the CON group, heparin cofactor 2 (SERPIND1), mannan-binding lectin serine protease 1 (MASP1), ficolin-2 (FCN2), and α1-Microglobulin/bikunin precursor (AMBP) were upregulated in patients with AMI and SAP, with a higher expression in AMI than in SAP. Additionally, human leukocyte antigen (HLA-C) was downregulated in both exosomes and plasma.ConclusionThe expression of four plasma exosome biomarkers in AMI and SAP patients was higher than that in noncoronary heart disease (NCHD) patients. HLA-C was downregulated in both exosomes and plasma, showing a potential to serve as a new candidate target for the detection and therapy of AMI.
Keywords: human leukocyte antigen (HLA-C)